Third Year Winner: The Weight of What We Carry: Shame as Survival in Two Histories of Oppression: EN 3430, South Asian Literature. Course Director: Vikrant Dadawala - Akbari, Donna (Noteworthy: The LA&PS Writing Prizes, 2025)
“The Weight of What We Carry: Shame as Survival in Two Histories of Oppression” is a strikingly researched and deeply felt essay that situates shame not merely as a byproduct of oppression, but as a social inheritance passed across generations. In its comparative reading of Baluta by Daya Pawar and Coolie Woman by Gaiutra Bahadur, the author investigates how shame operates as both burden and strategy—at once degrading and, paradoxically, protective. For Pawar, the structures of caste transmute into an internalized regime, one that polices speech, desire, and intimacy even as education offers the illusion of escape. His autobiography, as the essay shows, is not only testimony but also a candid exposure of how shame governs the smallest gestures of daily life. In Bahadur’s hybrid of history and memoir, silence becomes another inheritance, reframed as a kind of agency that women under indenture adopted to survive within hostile systems. What distinguishes this essay is its balance of close textual analysis with a willingness to dwell on the paradoxes of shame as both stigma and shield. The author’s argument moves fluidly between individual narrative and structural forces, linking Pawar’s refusal to speak to his mother in public with Bahadur’s effort to recover her great-grandmother’s silenced past. Together, these readings reveal that shame, once voiced, may transform into testimony—and that testimony into resistance. The result is an essay of unusual clarity and resonance, reminding readers that what is carried in silence may also be what sustains survival.